Hodgkin’s lymphoma: the role of cell surface receptors in regulation of tumor cell fate - Yurchenko, M.; Sidorenko, S.P. (Experimental Oncology, 2010)
The hallmark of Hodgkin’s lymphoma (HL) are mononucleated Hodgkin’s cells and multinucleated Reed-Sternberg (HRS) cells, which usually account for only about 1% of cells in the tumor tissue. The majority of HRS cells in classical HL are derived from germinal centre B cells that have acquired disadvantageous Ig variable chain gene mutations and escaped from apoptosis.